(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This study presents a detailed analysis of the selection and optimization of contact and interlayer materials for a hybrid energy conversion system that combines an indium tin oxide (ITO)-based photovoltaic (PV) cell with a thermoelectric (TE) module made of Bi₂Te₃/Sb₂Te₃. The main objective is to improve the overall energy efficiency of the hybrid structure by reducing contact resistance, enhancing heat transfer, and ensuring long-term reliability under thermal cycling conditions. To evaluate multilayer contact configurations such as Ni/Au, Ti/Ni/Cu, and Cr/Ag, the study employed realistic experimental parameters, along with ceramic interlayers composed of aluminum nitride (AlN) and aluminum oxide (Al₂O₃). The findings indicate that well-designed contact stacks can significantly minimize interfacial losses and thermal mismatch, achieving contact resistances as low as , while maintaining stable performance after 500 thermal cycles. Moreover, the hybrid PV–TE system demonstrated a notable improvement in total energy conversion efficiency, reaching approximately 9.1%, highlighting the synergistic contribution of both photovoltaic and thermoelectric components. Overall, this work provides practical design recommendations that can guide the future development of integrated PV–TE hybrid energy harvesting devices.